Plate X: Blood cells, arteries and veins under magnification - Baker, Henry (The Microscope Made Easy, 1743)
As described on accompanying pages listed next to the illustrations, this plate illustrates blood cells (figures I & II), arteries (figure III), veins (figure IIII), and platelets (figure V) under magnification. This plate comes from The Microscope Made Easy by Henry Baker (1698-1774), a book that popularized the microscope in the 18th century. The first section describes simple and compound microscopes along with how to prepare specimens and calculate their size. The second section introduces the reader to microscopy and the laboratory manual. Also includes "Animalcules," or microscopic animals, and anatomical discoveries made with the microscope.
Keywords: Baker, Henry, 1698-1774; Microscopy; Textbooks; Blood cells; Microscopes; Scientific apparatus and instruments; Arteries; Veins